Evaluation of bioadhesive properties of natural and modified banana starches (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A study was carried out on banana (Musa paradisiaca) natural and modified starches (pregelatinised and acetylated), to determine the potential bioadhesive properties of the starches in 0.1M hydrochloric acid and phosphate buffer (pH 6.8) to simulate the stomach and small intestine conditions, respectively using the rotating cylinder method. Starches were characterized using particle size, swelling capacity, bulk density, particle density, angle of repose, viscosity, and fourier transform infra-red spectroscopy, while the mechanical properties were determined using the crushing strength. The bioadhesive property of the starches were not related to the viscosity as the pregelatinised starch which was the least viscous had the longest time of detachment in both media. Physical mixtures of starches with polyvinylpyrollidone increased adhesion time significantly. Pregelatinised banana starch could be useful in the formulation of drugs targeted to the stomach, which when mixed with polyvinylpyrollidone increases adhesion time.
Keywords: Banana starch; pregelatinised starch; acetylated starch; modification; bioadhesion